Rapid single-step formation of liposomes by flow assisted stationary phase interdiffusion. (May 2018) - Has, Chandra; Phapal, Sopan M.; Sunthar, P.
Graphical abstract: Highlights: Density-driven convection creates a stationary interface for interdiffusion. Interdiffusion in water and ethanol phases leads to spontaneous liposome formation. LUVs (100–1000 nm) with PDI <0.2 prepared in a single step in 10 min. Diameter is robust and depends only on temperature and lipid type. Refined soy and egg lecithin mixtures yield 100–200 nm LUVs. Abstract: Laboratory preparation of unilamellar liposomes often involves multiple steps carried out over several hours to achieve a monodisperse size distribution. Here, we present a methodology based on a recently introduced lipid self-assembly principle—stationary phase interdiffusion (SPI)—to prepare large unilamellar vesicles (LUVs) of a monodisperse population in a short period of about 10 min. The stationary interface between a lipid–ethanol phase and an aqueous phase is created by a density difference induced convective flow in a horizontal capillary. The average size of the liposomes, as expected from the SPI principle, is modulated only by the temperature and the type of lipids. Lipid concentration, ethanol content, pH of the aqueous phase, and the time duration of the experiment have little influence on the mean diameter of the vesicles. This simple methodology can be easily carried out with a capillary and a micro-needled syringe and provides a rapid production tool for researchers requiring reproducible liposome suspensions. Refined natural lipids, based on soy and egg lecithin mixtures, yield LUVs in the range 100–200 nm, suitable for drug delivery applications.